Structural approach of social representations of teens on aging and elderly - Suiany Nascimento Mota; Jéssica de Menezes Nogueira; Bruna Karen Cavalcante Fernandes; Hanna Gadelha Silva; Márcia de Assunção Ferreira; Maria Célia de Freitas (Universidad de Alicante, 2018)
Objective: To know the social representations of adolescents on aging and elderly. Method: A descriptive study supported in Social Representations with the focus on its structural approach, performed in a state school of mid-level and the sample consisted of 99 adolescents. a questionnaire, called Words of Free Association Test (TALP) using terms like inducing aging and old words was applied. Data analysis was performed using as the tool EVOC 2000 software. Results: The results of TALP for inducing term "aging" is a list of 422 words, and of these 127 (30%) were different. We note that the word "old" appeared with the largest number of evocations (31), 73 words were mentioned only once. For inducing term "old", the result was a relationship with 418 words in total, and among these terms 151 (36.1%) were different. We found that the word "care" appears among the most cited with 22 evocations then comes the word "disease" being cited 17 times. Conclusion: For those teens aging process is strongly directed to the physical aspects as "white hair", "wrinkles", "old", which were very important positions mentioned and words.